Implementasi Materi Pembelajaran Pendidikan Agama Islam Dalam Penguatan Karakter Religius Siswa Di SMKN 1 Koto Balingka - Widi Wulandari; Iswantir M; Wedra Aprison; Salmi Salmi (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research is motivated by the problem of the religious character of students which is increasingly concerning and needs the attention of all parties, including educational institutions. The importance of character education requires PAI teachers to pay more attention to strengthening the religious character of students in schools, including students in class XI TITL 1 (Electrical Installation Engineering) at SMK N 1 Koto Balingka. The purpose of this study was to determine the implementation of Islamic Religious Education learning materials in strengthening the religious character of class XI TITL 1 students at SMKN 1 Koto Balingka, West Pasaman Regency and to determine the supporting factors and inhibiting factors for the implementation of Islamic Religious Education learning materials in strengthening the Religious Character of students in class XI TITL 1 At SMKN 1 Koto Balingka. This research uses a qualitative descriptive approach with a case study type of research. This research collects data by observation, interviews and documentation. Data analysis starts from data reduction, data presentation, and drawing conclusions. The results showed that the implementation of Islamic religious education learning materials in strengthening the religious character of class XI TITL 1 students at SMKN 1 Koto Balingka Pasaman Barat, namely through in-curricular activities and through extra-curricular activities. Supporting factors and inhibiting factors for the implementation of Islamic Religious Education learning materials in strengthening the religious character of class XI TITL 1 students at SMKN 1 Koto Balingka, West Pasaman district, are adequate libraries, classrooms and the presence of the Koran. The inhibiting factors are the students themselves who lack awareness in implementing religious activities at school, the backgrounds of students who differ in terms of religious understanding, the environment or student associations which tend to be less relevant to the process of strengthening students' religious character and inadequate places of worship.